Australasian College of Sports Physicians - A manual for Candidates (2007)
The Australasian College of Sports Physicians (formerly Australian College of Sports Physicians) is an incorporated body, registered in all States and Territories of Australia and New Zealand. It has an elected Council. Elections are held annually as determined by the College`s Articles of Association. The College has various committees including: • the Council, which is an elected body with overall responsibility for the affairs of the College; • the Board of Censors, which is responsible for overseeing the academic and clinical standards of the College; • the Examination Committee; which is a sub-committee of the Board of Censors and is responsible for the preparation and conduct of all ACSP examinations; and • the Training Committee, which is responsible for the accreditation and conduct of all aspects of the training program. Subject Areas in Sports Medicine The Board of Censors of the Australasian College of Sports Physicians has defined a number of broad subject areas of sports physician training with knowledge and skill components. These subject areas are as follows and are subject to further elaboration: 1. Anatomy 2. Biomechanics of Sports Techniques and Human Movement Analysis 3. The Physiology of Exercise 4. The Effects of Environment on Physical Activity 5. Exercise Prescription, Consultancy and Population Health 6. Pathophysiology of Injury and Repair 7. General Pathology of the Musculoskeletal System 8. The Pharmacology of Sport and Exercise 9. Physical Activity in Specific Populations 10. Disability and Physical Activity 11. Medical Aspects of Physical Activity in prevention of disease and maintenance of health a Indications, contra-indications and special precautions regarding physical activity in acute and chronic medical conditions b Internal Medicine, as it relates to Sport and Exercise 12. General Principles of Management of Injury in Sport, Exercise and Recreation 13. Sports Medicine Administration incl. Ethics/Medicolegal Considerations 14. Travel/Care of Elite Athlete 15. Biostatistics, Research Methods 16. Epidemiology of Sports Trauma 17. Psychosocial Aspects of Sport and Physical Recreation 18. Nutrition in Sport and Physical Activity 19. Sport Specific Issues 20. Professional Qualities of the Sport and Exercise Physician